Website Quality and Purchase Intention: The Role of Participation, E-Wom, and Trust - Suresh Kumar; Jessica Cindy Stacia; Yuyus Suriana; Diana Sari; Meydia Hasan (AFEBI Management and Business Review, 2020)
The purpose of this study is to find out the relationship between website quality, participation, electronic word of mouth, and trust to purchase intention in hospitality industry, particularly in the hotel industry. As far as the authors knowledge, the study about booking intention directly from hotel website based on website quality, participation, e-wom, and trust, has never been conducted before. In addition, most authors conducted booking intention based on online travel agent application leaving alone the hotel website. Thus, the loyalty of customers moves to online travel agency instead of the hotel itself.  Quantitative method has been conducted in this research. There were 68 item statements distributed to 380 respondents and 357 valid responses were received from respondents who stayed at any hotels for the past 6 months and booked a room directly from the hotel website. Data were checked for normality, model fit, construct validity and reliability. By applying some modifications, data were adequate for hypothesis analysis. This research reveals that website quality influences participation and trust, while participation influences e-wom on the online website, leading to customer’s trust which finally lead to customer’s purchase intention. This study contributes to the development of body of knowledge regarding purchase intention to book a room in a hotel directly from the hotel website based on website quality, participation, electronic word of mouth, and trust. Some recommendations were added to give more options for managers to increase the purchase intention to book a room from the hotel website. This study also recommends to add culture, location based advertising, social media marketing, and search engine optimization to increase the purchase intention to book a room directly from hotel website. Limitation of this study is on the scope where only Greater Jakarta was included, whereas there are other major cities in Indonesia that provide tourist attractions.